2019
DOI: 10.1016/j.ebiom.2019.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A sensitizes lung cancer cells to crizotinib through inhibition of the Ca2+/calcineurin/Erk pathway

Abstract: Background Crizotinib has potent anti-tumor activity in patients with advanced MET-amplified non-small cell lung cancer (NSCLC). However, the therapeutic effect is still not satisfying. Thus, developing approaches that improve the efficacy of crizotinib remains a significant challenge. Methods MET-amplified NSCLC cell lines were treated with crizotinib and cyclosporine A (CsA). Cell viability was determined by MTS assay. The changes of apoptosis, cell cycle and calcineu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 74 publications
(84 reference statements)
1
10
0
Order By: Relevance
“…A recent study revealed that when non-small cell lung cancer (NSCLC) cells were treated with crizotinib and CsA, apoptosis was promoted, and G2/M arrest was induced compared with crizotinib-only treatment. 148 In contrast, CsA and FK506 increased the risk of cancers in organ-transplant patients due to suppression of tumor immunosurveillance mechanisms. 49 For example, CsA treatment promotes the rapid growth and survival of renal cancer cells via activating Ras and inducing the expression of cytoprotective molecule heme oxygenase-1 (HO-1).…”
Section: Cancermentioning
confidence: 99%
“…A recent study revealed that when non-small cell lung cancer (NSCLC) cells were treated with crizotinib and CsA, apoptosis was promoted, and G2/M arrest was induced compared with crizotinib-only treatment. 148 In contrast, CsA and FK506 increased the risk of cancers in organ-transplant patients due to suppression of tumor immunosurveillance mechanisms. 49 For example, CsA treatment promotes the rapid growth and survival of renal cancer cells via activating Ras and inducing the expression of cytoprotective molecule heme oxygenase-1 (HO-1).…”
Section: Cancermentioning
confidence: 99%
“…Preclinical studies show that the tumor inhibitory mechanism of CsA involves the sensitization of lung cancer cells to crizotinib via suppression of the Ca2 + /CN/Erk pathway. Treatment with a combination of CsA and crizotinib might have potential in MET-amplified lung cancer (Liu et al 2019 ). CsA increases pancreatic cancer cell response to phospho-sulindac (P-S) treatment by overcoming NFATc1-mediated resistance (Murray et al 2014 ).…”
Section: Rcan1 and Cancer Therapymentioning
confidence: 99%
“…In the process of exploring their mechanisms, PP3 is identified as a target. , Before combining with PP3, CsA and FK-506 first form a binary complex with immunophilins, their specific carrier protein. Immunophilins are highly conserved and ubiquitously expressed with peptidylprolyl isomerase activity, and they are mainly divided into two types: cyclophilins (Cyp, for CsA binding) and FK-506 binding proteins (FKBPs). Recently, they were found to exhibit antitumor effects in cancers, including colorectal cancer, breast cancer, bladder cancer, lung cancer, , oral squamous cell carcinoma, and other cancers. , …”
Section: Small-molecule Modulators Of Pppasesmentioning
confidence: 99%
“…In addition, several tumor suppressor genes, such as p53, p21, and p27, are upregulated, and some oncogenic genes are downregulated, including cyclin D1, cyclin D3, and cyclin E. , CsA and FK-506 retard tumor growth by inhibiting proliferation, migration, and invasion and promoting apoptosis. In addition to evidence from the Masuo group, other evidence also revealed the antitumor activities of CsA and FK-506 on other cancers. , In a breast cancer model, pyruvate kinase M2 (PKM2) is overexpressed which is closely related to the usage of glycolytic intermediates for macromolecular biosynthesis and tumor growth. Treatment with CsA can significantly downregulate the expression of PKM2 and reduce ATP synthesis, which induces cancer cell necrosis .…”
Section: Small-molecule Modulators Of Pppasesmentioning
confidence: 99%
See 1 more Smart Citation